Quercetin triggers cell apoptosis-associated ROS-mediated cell death and induces S and G2/M-phase cell cycle arrest in KON oral cancer cells - Sukannika Tubtimsri; Tiraniti Chuenbarn; Suwisit Manmuan (BMC Complementary Medicine and Therapies)
Abstract Background Plant flavonoids such as quercetin are useful for both the therapeutic and preventive care of a variety of illnesses. Nevertheless, their antitumor efficacy against KON oral cancer is still unknown. Therefore, the aim of this investigation was to examine quercetin’s anti-growth, anti-migrative, and anti-invasive characteristics. The cell cycle arrest property and mitochondrial function disruption of quercetin were also investigated. Additionally, the cellular mechanism responsible for inducing apoptosis and the anti-metastasis mechanism were identified. Methods KON cells were treated with quercetin in order to test the anticancer activity of this compound. The MTT colorimetric assay was used to examine the cell viability of the treated cells in comparison to MRC-5 fibroblast cells. After being exposed to the detrimental effects of quercetin, the morphology of the KON cells was examined using DAPI and FDA double staining, as well as Hoechst 33,258 and AO double staining. Annexin V-FITC with a flow cytometer and DCFDA labeling were used to detect apoptosis induction and the ROS production associated with cell death. Quercetin’s ability to stop the cell cycle was evaluated via PI staining and the flow cytometer. The examination included anti-proliferative, anti-migration, and anti-invasion activities. Values for the transepithelial electrical resistance, or TEER, were measured. Ultimately, the mechanisms of action of the apoptotic markers and genes implicated in the metastatic process were clarified. Results Quercetin treatment reduced the vitality of KON cells and had minimal effect on MRC cells. Following quercetin treatment, the characterization of apoptosis and cell death in KON cells was observed. When quercetin was applied to KON cells, the generation of ROS increased. Furthermore, it was discovered that quercetin increased the percentage of dead cells and cell cycle arrests in the S and G2/M phases. Moreover, quercetin inhibited KON cells’ capacity for migration and invasion in addition to their effects on cell stability and structure. As a result of identifying the mechanism responsible for inducing apoptosis and preventing metastasis, quercetin was found to downregulate the expression of BCL-2/BCL-XL while increasing the expression of BAX. TIMP-1 expression was upregulated while MMP-2 and MMP-9 were downregulated. Quercetin’s anticancer properties and specific mechanisms of action in relation to KON cells were clarified. Conclusion Quercetin is greatly cytotoxic in oral cancer cells, triggering cells undergoing apoptosis and ROS-mediated cell death, possessing S and G2/M cell cycle arrest properties, and exhibiting anti-metastatic activities. Finally, this discovery opens up a wide range of possibilities for developing an anti-oral cancer drug and further investigating its effectiveness in vivo and in clinical trials as an alternative cancer treatment.